2017
DOI: 10.1093/jhered/esx063
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Evolution of the W Chromosome in Lepidoptera

Abstract: Moths and butterflies (Lepidoptera) represent the most diverse group of animals with heterogametic females. Although the vast majority of species has a WZ/ZZ (female/male) sex chromosome system, it is generally accepted that the ancestral system was Z/ZZ and the W chromosome has evolved in a common ancestor of Tischeriidae and Ditrysia. However, the lack of data on sex chromosomes in lower Lepidoptera has prevented a formal test of this hypothesis. Here, we performed a detailed analysis of sex chromosomes in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 58 publications
3
85
0
Order By: Relevance
“…For this system to function across such broad phylogenetic distances, splicing sites within the PBW dsx cassette must be recognized by endogenous splicing regulators within each of these two distantly related lepidopteran species. We therefore hypothesized that homologues of the key regulator of this splicing in silkworm, Masc, would also be present in DBMa species with a confirmed WZ/ZZ sex chromosome arrangement (Dalikova et al, 2017). Previous research on B. mori Masc identified the amino acid region between 304 and 310 aa and particularly the two cysteine residues (cysteinecysteine domain) as being necessary for promoting male-specific splicing of dsx .…”
Section: Introductionmentioning
confidence: 99%
“…For this system to function across such broad phylogenetic distances, splicing sites within the PBW dsx cassette must be recognized by endogenous splicing regulators within each of these two distantly related lepidopteran species. We therefore hypothesized that homologues of the key regulator of this splicing in silkworm, Masc, would also be present in DBMa species with a confirmed WZ/ZZ sex chromosome arrangement (Dalikova et al, 2017). Previous research on B. mori Masc identified the amino acid region between 304 and 310 aa and particularly the two cysteine residues (cysteinecysteine domain) as being necessary for promoting male-specific splicing of dsx .…”
Section: Introductionmentioning
confidence: 99%
“…The Z chromosome resembles autosomes and contains many genes. Multiple studies have shown a highly conserved synteny of Z-linked genes between species across the phylogenetic tree of Lepidoptera [2][3][4][5]. In contrast, the W chromosome is largely composed of repetitive sequences and is partially or completely degenerated, possibly as a result of the absence of recombination in lepidopteran females [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the origin of the W chromosome remains elusive. There are several hypotheses about when and how the W chromosome arose [5,11,12]. The generally accepted hypothesis of Lukhtanov [12] assumed that the W chromosome evolved in a common ancestor of Tischeriidae (Tischeriina in the original paper), a small group of leaf-mining moths, and Ditrysia, an evolutionary younger, multidiverse group comprising 98% of lepidopteran species.…”
Section: Introductionmentioning
confidence: 99%
“…Endoclita excrescens belongs to a primitive lepidopteran family, the Hepialidae, which is one of the key families to elucidate the origin of the lepidopteran W chromosome (Lukhtanov ; Dalíková et al . ; Fraïsse et al . ).…”
Section: Discussionmentioning
confidence: 99%